"It's Largely a Rigged System": Voter Confidence and the Winner Effect in 2016. (December 2018) - Sinclair, Betsy; Smith, Steven S.; Tucker, Patrick D.
The 2016 presidential election provided a unique opportunity to revisit two competing hypotheses for how voters establish their perceptions of electoral integrity. First, mass public opinion is believed to derive from elite messages. In the 2016 presidential campaign, candidate Donald Trump maintained that the election system was "rigged, " while election administration experts and officials received considerable media coverage in their efforts to counter Trump's claims. Second, literature on voter confidence has established a "winner effect"—voters who cast ballots for winners are more likely than voters on the losing side to believe their vote was counted correctly. Thus, voters were exposed to two theoretically opposite effects. In this paper, we find that the "winner" effect mitigates the effects from strong pre-election cues from elites. We also show the effect of pre-election attention to the rigging issue, find a symmetry of the election outcome effect for winners and losers, and reconsider our explanations of the winner effect. Finally, we go beyond the existing studies of the winner effect to consider the kind of citizens who are most susceptible to that effect.